Evidence of Financial Ratio Impact on Non-Financial Firm Profitability - Muchamad Syafruddin; Clarientina Jane Weinanto; Haryani Haryani (Accounting Analysis Journal, 2023)
Purpose: This study is conducted to determine the factors that affect profitability in Indonesia listed companies by using financial ratios. Four independent variables (liquidity, intangible assets, working capital, and company leverage) were empirically tested to determine their relationships with profitability. Method: The data set covers 100 companies during the period of 2019 – 2021, and a random selection method was used in order to achieve credibility and fairness as much as possible and hypotheses were tested using a pooled ordinary least square regression model Findings: These findings show that firm size, working capital, and firm efficiency have a positive and significant relationship with profitability. In addition, these findings show a negative and significant relationship between liquidity and EPS and debt to equity ratio with ROA and EPS, but show a negative insignificant relationship with ROA. This means that the company suffers from low profitability due to the inefficient use of current assets. Interestingly, leverage shows mixed results, debt to equity ratio shows a negative and significant relationship with ROA and EPS, while leverage ratio shows a positive but insignificant relationship with ROA and EPS. In other words, profitability will increase only up to certain point. Novelty: This study differs than previous studies in number of aspects: First, this study examines the impact of four independent factors and two control variables that some of them are new in the context of research in Indonesia such as intangible assets. Second, previous studies focus on financial industry such as banks, however this study focuses on non-financial industry. Keywords: Financial Ratios; Profitability; Nonfinancial Companies; Indonesia